Pelatihan Dasar Komputer dan Aplikasi Office untuk Siswa MTs.S Annurain Tondowolio Kolaka - Zainuddin, Noorhasanah; Muchtar, Mutmainnah; Utomo, Puji Prio; Rustan, Fathur Rahman; Jimsan; Rasyid, Rasmiati; Mardiawati; Iin, Johar Nur; Ningsi, Nurfitria (TENANG : Teknologi, Edukasi, dan Pengabdian Multidisiplin Nusantara Gemilang, 2024)
Information technology has become a fundamental skill that is essential for the younger generation to master in order to keep up with the advancements of the times. This basic computer and Office application training aims to enhance the skills of MTs.S Annurain Tondowolio students in operating computer hardware as well as Microsoft Word, Excel, and PowerPoint applications. The training was conducted by a team of lecturers and students from the Universitas Sembilanbelas November Kolaka using a teaching method that includes theoretical explanations, demonstrations, and hands-on practice. The students were equipped with knowledge about computer hardware, including input and output devices, as well as how to use Office applications for academic and administrative purposes. Evaluation was carried out through practical tests and filling out questionnaires to assess students' understanding of the training material. The evaluation results showed that the majority of students were able to master the basic skills in using the applications taught and understood the use of computer hardware well. Based on these results, it can be concluded that this training successfully improved students' abilities in using information technology and can serve as a foundation for further skill development in the future.